Penambahan Tepung Daun Talas dalam Ransum Terhadap Kadar Air dan Susut Masak Daging Itik Mojosari - Jumaidil; Rasbawati; Semaun, Rahmawati (Edupedia Publisher, 2024)
Dependence on expensive conventional feed ingredients encourages substitution with local feed ingredients, including taro leaves. This study examines the effect of adding taro leaf flour (Colocasia esculenta) to the ration on the water content and cooking loss of Mojosari duck meat. The method used was a completely randomized design with four treatments, namely 0% (control), 1%, 3%, and 5% taro leaf flour. Each treatment was repeated five times. The addition of taro leaf flour had a significant effect on the water content and cooking loss of duck meat. The water content of duck meat in the treatment was 0% (68.53%), 1% (69.82%), 3% (69.29%), and 5% (70.37%). The cooking loss of duck meat in the treatment was 0% (16.66%), 1% (20.00%), 3% (23.33%), and 5% (26.66%). From these results, it can be seen that the addition of 1% taro leaf flour did not provide a significant difference in water content and cooking loss compared to the control, while the addition of 3% and 5% gave significantly different results. The addition of 1% taro leaf flour to the ration is the best in maintaining meat quality significantly so it is worthy of being used as an alternative feed ingredient.